Rigidez normativa e circuito inferior em Maringá (PR) : territórios, atividades e atores - Postali-Santana, Valéria Barreiro (2013)
The cities shelter diferent divisions of work, which are explained by distinct but interdependent logics. Juxtaposed in the built environment, we can find multiple blended ways of production, distribution and consumption done by differentiated techniques and ways of organization. According to Santos (1979), the segmentation which is present in the cities of the undeveloped countries, related to the possibilites of contenting the needs, creates qualitative and quantitative differences in the consumption, which are the cause and effect of the existence and maintenance of two economic circuits, the superior and inferior ones. Santos (1979) understands that the superior circuit constitutes a direct result of the modernizations which affects the territory, the inferior circuit comprises the ways of manufacture of non intensive funds, the simplest ways of services that are offered to retail and commerce of little dimensions, overcoat turned to the poor population consumption. In moving forwards the superior circuit is fed by the global contemporary acceleration, the inferior circuit is molded by time and shapes of the place. In the present work, we searched to identify an analysis wich was concerned to the dynamics that run through and define the inferior circuit of the economy in the city of Maringá, in light of variables which characterize the current period, namely, the technique, the information, the comsumption, the publicity and finances (SILVEIRA, 2008; 2009) meantime normative rigour practiced by the local public authorities, condition that confers important peculiarities to the inferior circuit of the city of Maringá, which distinguishes it from the reality of this economic subsystem founded in the other Brazilian cities.